Mental Health Awareness and Employee Welfare: The Role of Work Engagement and HR Management Support - Kurniawan, Ade; Yudiansyah, Irene Abelianata; Rifai, Rafly Ahmad; Ramdani, Ahmad (GLOBAL: Jurnal Lentera BITEP, 2025)
This research examines the influence of Mental Health Awareness on employee welfare with Work Engagement as a mediating variable and HR Management support as a moderating variable. Through a quantitative approach with survey method, the research involved 103 respondents selected using simple random sampling technique from a population of 615 employees. Data analysis using SmartPLS 3.0 revealed that Mental Health Awareness significantly influences employee welfare, work engagement, and perception of HR management support. However, the results did not find significant mediating effects of work engagement or moderating effects of HR management support in the relationship between mental health awareness and employee welfare. These findings emphasize the importance of implementing mental health awareness enhancement programs as a primary strategy in optimizing employee welfare in the FMCG industry environment.